Implementation of evidence-based practice in paediatric nursing care: facilitators and barriers - Torres, Cânia (2024)
Background: Evidence-based practice (EBP) is widely recognised in healthcare as a means of improving patient outcomes by incorporating patient preferences, clinical experience, and rigorous research. Although it has demonstrated potential in promoting healthcare, increasing patient safety, and reducing costs, there are still challenges in implementing and applying EBP in practice. The aim of this study was to explore the barriers and facilitators identified by nurses concerning the implementation of EBP in the care provided to children and their families. Methods: Two focus groups were held with a total of 32 nurses from a paediatric unit of a university hospital. The qualitative data were organised using NVivo, and thematic analysis was undertaken following Bardin’s three-phase process. Findings: Three categories emerged: Facilitators for the Implementation of EBP, Barriers to the Implementation of EBP, and Family and Child-Centred Care in Clinical Practice. The main facilitators are the presence of mentors, institutional recognition, an environment that promotes EBPs, and the interest and motivation of the team. The main barriers highlighted were unassertive intradisciplinary and inter- disciplinary communication, time management, tradition, and inexperience in research. Organisations must implement policies that promote environments conducive to EBP. Conclusion: It is crucial to prioritise ongoing professional development, integrate this practice into nursing education, promote innovative organisational cultures, and embrace the principles of Family-Centred Care. Nurses recognise the importance of mentors as key to implementing this practice.